2020
DOI: 10.1080/17436753.2020.1732622
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-drying preparation of porous diatomite ceramics with high porosity and low thermal conductivity

Abstract: Hierarchically porous diatomite ceramics were fabricated by the freeze-drying method using Xanthan Gum as a gelling agent. They showed high porosity of 84.8-92.7% and a low thermal conductivity value of 0.061-0.123 W m −1 K −1 (tested at 473-1073 K). Their compressive strength increased with increasing the preparation temperature and/or the solid loading level. The porous sample with 15 wt-% solid loading, after 2 h firing at 1373 K, showed a porosity level of 92.7%, a compressive strength of 0.11 ± 0.01 MPa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…As described above (Figures 7 and 8), the obtained samples in this case possessed reasonable mechanical strength and thermal conductivity. To get an intuitive performance of the present foams, the results were respectively compared with the various diatomite porous ceramics similarly prepared from materials containing mesoporous structure reported in the literature based on the ratio of thermal conductivity to specific strength [11][12][13] (in Table 1), the smaller the thermal conductivity to specific strength ratio (slope), the higher the strengths and better thermal insulation performance of the sample. When compared with the reported diatomite porous ceramics with hierarchical pore structures possessing close or lower thermal conductivity values, the current samples exhibited higher specific strength (3.4-4.2 MPa cm 3 g −1 vs 0.7-3.1 MPa cm 3 g −1 ) and smaller slope (0.028-0.031 g/ (m s °C) vs 0.031-0.089 g/(m s °C)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above (Figures 7 and 8), the obtained samples in this case possessed reasonable mechanical strength and thermal conductivity. To get an intuitive performance of the present foams, the results were respectively compared with the various diatomite porous ceramics similarly prepared from materials containing mesoporous structure reported in the literature based on the ratio of thermal conductivity to specific strength [11][12][13] (in Table 1), the smaller the thermal conductivity to specific strength ratio (slope), the higher the strengths and better thermal insulation performance of the sample. When compared with the reported diatomite porous ceramics with hierarchical pore structures possessing close or lower thermal conductivity values, the current samples exhibited higher specific strength (3.4-4.2 MPa cm 3 g −1 vs 0.7-3.1 MPa cm 3 g −1 ) and smaller slope (0.028-0.031 g/ (m s °C) vs 0.031-0.089 g/(m s °C)).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the sintering temperature of the ceramic sample is closely related to the chemical composition of the raw materials. Moreover, our previous research results showed that the specific strength (the specific strength was defined as the ratio of the compressive strength to the density of the sample) and the required temperature of diatomite porous ceramics prepared by the same diatomite as the raw material through the foam-gelcasting [11], freeze-drying [12] and adding sintering aids [13] routes are respectively of 3.1 MP cm 3 g −1 and 1100 o C, 0.7 MP cm 3 g −1 and 1100°C, and 2.5 MP cm 3 g −1 and 600°C, revealing that the moulding methods and additives will also affect the preparation temperature and mechanical properties of the ceramic sample to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“… 68 Its chemical composition is mainly SiO 2 . Its microporous structure and active silica components make diatomite widely used in the fields of adsorption, 69 purification, 70 thermal insulation, 71 sound absorption, 72 filtration 73 and energy storage. 18,74 …”
Section: Application Of Natural Minerals In Libs Separatormentioning
confidence: 99%
“…Anisotropic properties can be introduced to two-dimensional materials through processes such as the template method, with one common approach being the ice template method, [37,38] oriented assembly, [39,40] and freeze-drying. [41,42] For example, Qian et al used a freeze-drying technique to prepare h-BN porous scaffold, subsequently preparing phase change composites by infiltration of paraffin wax into h-BN porous scaffolds with continuous thermal conductivity paths. The results showed that the 3D network with h-BN scaffolds enhances thermal conductivity to a great extent through their continuous thermal conductivity paths.…”
Section: Introductionmentioning
confidence: 99%